2005 BJCA survey of cardiology trainees - Myerson, S (2006)
The second annual survey from the British Junior Cardiologists' Association (BJCA) has new data on several areas, including the European Working Time Directive, modernising medical careers, and careers in academic cardiology. The surveys are becoming a strong and influential voice in cardiology. Last year's survey was noted by many national bodies, including the British Cardiac Society (BCS) and the Royal College of Physicians. Over a third of BJCA members responded to this year's survey and Dr Saul Myerson, BJCA President, highlights some of this year's trends.